Challenges and Opportunities for Community Empowerment in The Era of Society 5.0 - Suryadi Suryadi (Prosperity: Journal of Society and Empowerment, 2022)
Society 5.0 is a technology-based human-centered society concept. In this case, there has been rapid technological development, including human roles being replaced by intelligent robots. Artificial intelligence will transform millions of data collected through the internet in all areas of life through Society 5.0. It is to increase human capacity in opening up opportunities for humanity. This article was qualitative research with a literature review method to assist a researcher in providing an overview of the context of or current issues. Research data sources were journals, articles, books, and other relevant references. Data collection techniques were carried out by using literature study and documentation. The data analysis technique began with accessing the data, organizing, sorting, categorizing, and classifying the collected documentation studies. Various problems arose in the Era of Society as an extraordinary challenge in preparing the existing human resources. If human resources were fulfilled, then the various opportunities for sustainable advancement of IT would be more easily felt by the community so that they could face humans to live, grow, and prosper through collaboration between machines and co-creation. Therefore, it was necessary to strengthen community empowerment through cooperation between elements, including government, non-governmental organizations, political parties, community organizations, and educational institutions, as provisions for the development process in facing the challenges of entering Society 5.0.